2018
DOI: 10.1097/ncq.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Barcode Medication Administration Technology That Contribute to Patient Safety

Abstract: In an effort to prevent medication errors, barcode medication administration technology has been implemented in many health care organizations. An integrative review was conducted to understand the effect of barcode medication administration technology on medication errors, and characteristics of use demonstrated by nurses contribute to medication safety. Addressing poor system use may support improved patient safety through the reduction of medication administration errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Adherence to the principles of patient safety and the prevention and reduction of practice errors have been facilitated by technological solutions in recent years [31,32]; however, suboptimal quality and safety of care remain evident, indicating the need for improved understandings of the various factors and conditions that increase adherence in daily nursing practice [33]. Consequently, this review aimed to retrieve, explore, and synthesise factors evident in the international literature that influenced nurses' adherence to patient-safety principles.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to the principles of patient safety and the prevention and reduction of practice errors have been facilitated by technological solutions in recent years [31,32]; however, suboptimal quality and safety of care remain evident, indicating the need for improved understandings of the various factors and conditions that increase adherence in daily nursing practice [33]. Consequently, this review aimed to retrieve, explore, and synthesise factors evident in the international literature that influenced nurses' adherence to patient-safety principles.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the benefit of technology can be hampered if there is resistance from employees to use it properly (39) . Allied to this, the use of a barcode system, which identifies medication, can support safe administration of drugs (40) .…”
Section: C) New Technologies Used In the Work Process To Minimize Medmentioning
confidence: 99%
“…Electronic medication management systems have been recognized as valuable tools in optimal healthcare provision, decreasing turnaround time, increasing efficiency and, most notably, reducing error rates (Franklin et al 2007;Seibert et al 2014;Strudwick et al 2018). However, the published evidence on the effectiveness of BCMA and full CLMS have been limited, and some studies have reported no change in medication error rates before and after implementation of these technologies (Bowers et al 2015;Helmons et al 2009).…”
Section: Medication Safety Technologiesmentioning
confidence: 99%